Combination of Cloxacillin and Essential Oil of Melaleuca armillaris as an Alternative Against Staphylococcus aureus - Buldain, Daniel; Buchamer, Andrea V.; Marchetti, María L.; Aliverti, Florencia; Bandoni, Arnaldo; Mestorino, Nora (Frontiers in Veterinary Science, 2018)
The emergence of resistance to antibiotics has been favored by abuse in the application of antimicrobials in human and animal medicine. Essential oils are a great resource to deal with this crisis. Melaleuca armillaris belongs to the family of Myrtaceae, rich in species with essential oils. Plant extracts has shown antimicrobial activity in many investigations. Cloxacillin (CLOX) is an antibiotic widely used in veterinary medicine against Staphylococcus aureus. Our aim was to assess pharmacodynamic interaction established by combining essential oil of M. armillaris (EO) with CLOX in search of a synergistic effect that maximizes the antibacterial activity against S. aureus. The EO was obtained by steam distillation and its composition was analyzed by a GC–FID–MS. The most abundant components in the EO were 1.8 cineole (72.3%), limonene (7.8%). and α-pinene (6%). We worked with wild type S. aureus strains (n = 3) isolated from Holstein cows, and S. aureus ATCC 29213 as the reference strain. The Minimum Inhibitory Concentration (MIC) of CLOX, EO and the combination was determined by microdilution in broth at pH 7.4; 6.5 and 5.0. The checkerboard method was applied to evaluate the interaction between CLOX and EO. The Fractional Inhibitory Concentration index (FIC) was established. From those combinations that yielded the lowest FIC values, we evaluated the index of antibacterial activity (E), established as the difference between the Log10 values of the number of viable bacteria at the initial (nt0) and at the end of the test (nt24). So, time-killing curves with CLOX and EO/CLOX combination at 0.5, 1, 2, 4, and 8 fold the MIC in broth at pH 7.4; 6.5 and 5.0 were prepared. We considered Bacteriostatic effect (E = 0) Bactericidal effect (E = −3) and Effect of virtual eradication of bacteria (E = −4). A clear synergic activity between the EO and the CLOX was demonstrated, which allows reducing the MIC of β-lactam against S. aureus. This interaction was favored by acidification of the medium, where lower concentrations of CLOX achieved a bactericidal effect, close to virtual eradication, in the presence of small amounts of EO.